The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.2527/1992.7082533x
|View full text |Cite
|
Sign up to set email alerts
|

Digestion, feed intake, and live weight gain by cattle consuming bermudagrass hay supplemented with whey

Abstract: Three experiments were conducted with cattle consuming bermudagrass hay to determine whether low-level supplements of whey alone, corn alone, or whey plus corn affect feed intake, digestion, and(or) BW gain. Six ruminally and duodenally cannulated beef cows (574 kg), used in a Latin-square trial (Exp. 1), were fed bermudagrass hay without supplementation (control) or with 2.8% whey (low whey, LW), 5.6% whey (high whey, HW), 17.4% ground corn (C), 2.8% whey plus 14.9% corn (C-LW), or 5.6% whey plus 12.4% corn (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Nutrient digestibilities of T85 and CBG reported by Hill et al (1996Hill et al ( , 1997 by beef steers were lower than those observed in the present study. However, the digestibilities of OM, NDF, and CP reported in our study for CBG are in agreement with those observed by other workers with growing Holstein steer calves or beef cows (Galloway et al, 1992(Galloway et al, , 1993aForster et al, 1993).…”
Section: Intake and Digestion Of T85 And Cbg By Growingsupporting
confidence: 93%
“…Nutrient digestibilities of T85 and CBG reported by Hill et al (1996Hill et al ( , 1997 by beef steers were lower than those observed in the present study. However, the digestibilities of OM, NDF, and CP reported in our study for CBG are in agreement with those observed by other workers with growing Holstein steer calves or beef cows (Galloway et al, 1992(Galloway et al, , 1993aForster et al, 1993).…”
Section: Intake and Digestion Of T85 And Cbg By Growingsupporting
confidence: 93%
“…Feed conversion ratio expressed as g TDN /g gain had the same trend. These results are in harmony with those suggested by Galloway et al (1992) and Titus et al (2000). Data of economical evaluation of feeding growing lambs on experimental rations are summarized in Table(5) .…”
Section: Second Experimentsupporting
confidence: 84%
“…while after 4 hrs., concentration of TVFA's was the highest significantly (P<0.05) in FSLCW + PEG (T 4 ), being 13.0 meq /100 mL rumen liquor. Higher TVFA's concentrations as a result to FSLCW and PEG supplementation may be attributed to their ability to improve the digestibility of most nutrients in the rumen (Galloway et al,1992 andSalawu et al, 1997). Supplementation of whey protein as a rapid degradable protein may be a supplier of a specific amino acids or peptides (limiting bacterial growth) which are used to form branched-chain VFA that are required by certain bacteria for optimum growth and so optimum microbial protein synthesis (Stock et al, 1986).…”
Section: Second Experimentmentioning
confidence: 99%
“…Whey protein (WP) is a byproduct of the manufacturing process of cheese with a high content of soluble lactose (37% to 72%) [5,6]. WP can increase the entities of protozoa, which increases the utilization of carbohy-drates in ruminant feeds [79].…”
Section: Introductionmentioning
confidence: 99%
“…According to earlier study, WP increases the concentration of butyric acid and milk fat precursors which ferment carbohydrate in the rumen of milk cows [14]. The addition of WP to feed based on grain and grass [15] or low-quality hay [6] was reported to increase the weight and organic intake of beef calves. In the paper by Miron et al [16], it was claimed that this is because the inflow of WP with ample lactose into the rumen increases the creation of bacteria and protozoa which use WP as an energy source, helping decompose the cell wall with a high ratio of structural carbohydrate.…”
Section: Introductionmentioning
confidence: 99%